2020
DOI: 10.4102/phcfm.v12i1.2560
|View full text |Cite
|
Sign up to set email alerts
|

CLEVER maternity care: A before-and-after study of women’s experience of childbirth in Tshwane, South Africa

Abstract: Background: Birthing care matters to women and some women experience mistreatment during childbirth.Aim: To determine the effect the ‘CLEVER Maternity Care’ package, a multi-faceted intervention to improve respectful, quality obstetric care.Setting: Ten midwife-led obstetric units in Tshwane health district, South Africa; five intervention and five control units.Methods: We conducted an anonymous baseline and end-line survey to measure the change in women’s perceptions and experiences of childbirth care after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 35 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…Owing to the wide range of methodological inadequacies of the studies, all selected reports were included in the analysis for pragmatic reasons, which were relevant to the aim of the review and comprised the highest available methodological rigor of all assessed studies. Three of the 12 included studies were RCTs [ 22 , 36 , 38 ], and the remaining nine were pre-and-post/ quasi experimental studies [ 23 , 33 35 , 37 , 39 42 ]. Out of the 12 studies included, it is worth noting that regardless of no criteria used to exclude studies based on their geographical region, eleven studies were conducted in sub-Saharan Africa (specifically, in Ethiopia, Tanzania, South Africa, Ghana, Kenya, and Sudan) and one study was conducted in India.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the wide range of methodological inadequacies of the studies, all selected reports were included in the analysis for pragmatic reasons, which were relevant to the aim of the review and comprised the highest available methodological rigor of all assessed studies. Three of the 12 included studies were RCTs [ 22 , 36 , 38 ], and the remaining nine were pre-and-post/ quasi experimental studies [ 23 , 33 35 , 37 , 39 42 ]. Out of the 12 studies included, it is worth noting that regardless of no criteria used to exclude studies based on their geographical region, eleven studies were conducted in sub-Saharan Africa (specifically, in Ethiopia, Tanzania, South Africa, Ghana, Kenya, and Sudan) and one study was conducted in India.…”
Section: Resultsmentioning
confidence: 99%
“…All quasi-experimental studies scored positive ('Yes') for more than half of the appraisal domains, ranging from five to seven of nine quality domains. In four out of nine quasi-experimental studies [ 23 , 33 , 37 , 39 ], the participants in the comparison groups were not similar. In contrast, all studies identified causes (interventions) and effects (mistreatment and/or respectful maternity care).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Continue expansion of psychosocial support via NurseConnect mobile health application supported by National Department of Health [ 49 ]. • Identify lessons learned from the CLEVER Maternity Care intervention, which aims to increase respectful, quality obstetric care [ 50 ]. Sociocultural • Increase awareness and availability of support from doulas: trained professionals who provide culturally competent, continuous physical, emotional and informational support to mothers before, during and shortly after childbirth.…”
Section: Resultsmentioning
confidence: 99%
“…• Identify lessons learned from the CLEVER Maternity Care intervention, which aims to increase respectful, quality obstetric care [ 50 ].…”
Section: Resultsmentioning
confidence: 99%